Intentions for post-abortion contraceptive use among women who received abortion services in health facilities of Harar city and Dire Dawa city - Degefa, Meron; Assefa, Nega; Deresa, Merga; Abebe, Dawit; Mesfin, Sinetibeb (Frontiers in Global Women's Health, 2025)
BackgroundA woman's specific beliefs about contraceptives influence her engagement and adherence to these methods. The intention to use post-abortion contraceptive methods is a critical aspect of reproductive health, particularly for women who have undergone abortion procedures. The use of less effective contraceptive methods, inconsistent usage, and discontinuation significantly contribute to unintended pregnancies, which are a primary cause of abortion. Studies indicate low contraceptive utilization and a high prevalence of abortion in the study area. Therefore, this study aimed to assess the intention to use post-abortion contraceptives and the associated factors among women visiting health facilities for abortion services, utilizing a behavioral model.ObjectiveTo assess intention to use post abortion contraceptive use and associated factors among women visiting health facilities for abortion services in Harari region and Dire Dawa City Administration, eastern Ethiopia.MethodsAn institutional-based cross-sectional study was conducted among 609 women who received abortion services in the Harari region and Dire Dawa city administration health facilities. All women who sought abortion services at these health facilities during the study period were included in the research. Data were collected using a structured, interviewer-administered questionnaire. Binary logistic regression was employed to predict the association between dependent and independent variables. Variables with a p-value of less than 0.05 were considered statistically significant.ResultThe overall prevalence of intention to use post abortion contraceptive of women came for abortion service was 74.7% (95% CI: 71.3–78.2). Women who had contraceptive use history [AOR 2.580; 95%CI (1.216–5.473)], no pregnancy plan within the next two years [AOR 2.859; 95%CI (1.451–5.635)], positive attitude [AOR 3.335; 95%CI (1.831–6.077)], high level of subjective (perceived) norm [AOR 3.348; 95%CI (1.805–6.210)], high level of perceived behavioral control [AOR 6.784; 95%CI [(3.650–12.607)] were positively associated with intention to use post abortion contraceptive. Women who were divorced [AOR 0.149; 95%CI (0.039–0.578)] and had wanted pregnancy abortion [AOR 0.336; 95%CI (0.153–0.735)] variables were negatively associated with intention to use post abortion contraceptive.ConclusionThis study revealed that more than two-thirds of the participants expressed an intention to use contraception following an abortion. Healthcare providers should offer comprehensive education and counseling on contraceptive options for women post-abortion. Furthermore, it is essential to provide personalized counseling to address each woman's unique needs and concerns regarding contraceptive choices.